135k views
3 votes
I need help with this

I need help with this-example-1
User Joe Huang
by
5.4k points

1 Answer

7 votes
You can solve the equation for y:
y = (12 - 4x)/-3 = (4/3)x - 4
And for x:
x = (12 + 3y)/4 = (3/4)y + 3

Now for ...
x=0, y = (4/3)·0 -4 = -4
y=0, x = (3/4)·0 +3 = 3
x=9, y = (4/3)·9 -4 = 12-4 = 8
y=-8, x = (3/4)·(-8) +3 = -6 +3 = -3


\begin{array}cx&y\\0&-4\\3&0\\9&8\\-3&-8\end{array}
User Miroslav Kovac
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.